KARAKTERISTIK LINGKUNGAN, MOTIVASI KERJA DAN KOMPETENSI PHT PENYULUH PERTANIAN SWADAYA SERTA PENGARUHNYA PADA KINERJA DALAM DIFUSI PHT DI SENTRA PRODUKSI SAYURAN CIANJUR DAN BANDUNG - Nawangwulan Widyastuti; Lukman Effendy (Jurnal Penyuluhan Pertanian, 2020)
The aims of this research are: (1) To explain the effect of environment characteristic, motivation and competency of the work to performance of voluntary extension worker in the diffusion of Integrated Pest Management (IPM) in district of Cianjur and Bandung (2) To explain the relationship of environment characteristic, motivation, competency of the work and performance of voluntary extension worker in the diffusion of Integrated Pest Management in district of Cianjur and Bandung. This research was carried out in May through November 2010. Result of this research showed that: (1) Environment characteristic and competency of IPM gives significant effect on the work of voluntary extension worker in the dissemination IPM in Cianjur and Bandung district. Environment characteristic was represented by community perception on the role of voluntary extension worker and support of local informal leader. Competency of IPM was manifested by the ability to anticipate and to prevent the attack of pest. Work motivation of voluntary extension worker provide in significantly on the performance to indicators which can be use to evaluate work motivation are reward and willingness achieve best (2) Environment characteristic and competency IPM show strong relationship in the influence of performance of voluntary extension worker.